(untitled) (Research, Society and Development, 2022)
Introduction: Delirium is a transient neuropsychiatric syndrome considered a geriatric emergency, related to prolonged periods of hospitalization and which contributes to an increase in the mortality rate, especially in the elderly affected by SARS-CoV-2. Objective: To carry out an integrative review of the literature in order to list factors of importance of screening, anamnesis and physical examination to contain the early manifestation of delirium in elderly patients affected by Covid-19. Methodology: This is an integrative literature review carried out by searching for scientific articles in Pubmed (NCBI), Latin American and Caribbean Health Sciences (Lilacs) and Scientific Electronic Library Online (SciELO) databases.). For this, the descriptors were used: Coronavirus, Delirium, Elderly and the filter “PUBLICATION DATE” was selected with the option “5 YEARS”, in the aforementioned databases. The articles selected through the PICO strategy were submitted to methodological rigor and level of evidence analysis. Results: 155 scientific articles were found; however, 17 articles were selected after analyzing the inclusion and exclusion criteria. Of this sample, 41, 17% of the selected studies reported that delirium is associated with high mortality and morbidity, in addition to being often underreported. Screening using tools such as the Chart-Based Delirium Identification Instrument is essential for early detection of delirium. Conclusion: Multiprofessional team work aligned with medical work is necessary for early intervention of delirium in elderly patients with Covid-19.